Characterization of Silver Nanoparticles Prepared via Green Synthesis from Amomum Subulatum: Investigation of its Antioxidant, Antimicrobial and Catalytic Properties in Dye Degradation - Baghel, Sonam; Khurana, Monika; Gupta, Prachi (Masyarakat Katalis Indonesia - Indonesian Catalyst Society (MKICS), 2025)
The seeds extract of Amomum Subulatum commonly known as black cardamom is used for preparing Silver Nanoparticles (AgNps) via green route. The characterization of these nanoparticles was done by UV-visible, Fourier transform Infrared (FTIR) spectroscopy, X-ray diffraction (XRD) and Transmission Electron Microscopy (TEM) techniques. The UV-vis spectra showed sharp absorption maximum at 432 nm that confirmed that AgNPs were synthesized successfully. The TEM measurements indicated that AgNps are mostly spherical with a few having hexagonal and trigonal shapes with size range of 13-21 nm. Dynamic Light Scattering (DLS) confirmed the stability of AgNps having negative zeta potential. XRD confirmed the mono-crystallinity of the prepared AgNps. A significant zone of inhibition is observed by these nanoparticles against gram positive and gram-negative bacteria. These nanoparticles exhibit a significant catalytic activity with respect of 4-nitrophenol (4-NP). The synthesized AgNps act as a catalyst and degraded the organic dyes, Methylene Blue (MB) and Methylene Orange (MO) by Sodium borohydride (NaBH4) as confirmed by UV-vis spectroscopy. Copyright © 2025 by Authors, Published by BCREC Publishing Group. This is an open access article under the CC BY-SA License (https://creativecommons.org/licenses/by-sa/4.0).